Economic Challenges Of The Republic Of South Sudan - bachraoui, mestapha (The journal of Teacher Researcher of Legal and political Studies, 2024)
In this study focuses on the problems and obstacles encountered by the republic of South Sudan after the secession, which has drawn the country into a vicious cycle of civil war, in addition to tackling the various bets and challenges facing the state of South Sudan, in a sincere desire for the sons of the nascent state to advance in the construction of a stable state. The study found that the state of weakness in the particular in the light of the economic capacities available in the presence of state of South Sudan was due to the failure of government policies based on the control of people's resources which were based in its programs on tribal and ethnic prejudices, and the deprivation of many groups of their legitimate economic rights, which has contributed to the spread of violence and lack of stability. Dans cette étude se concentre sur les problèmes et les obstacles rencontrés par la République du Soudan du Sud après la sécession, qui a entraîné le pays dans un cercle vicieux de guerre civile, en plus de s'attaquer aux divers paris et défis auxquels l'État du Soudan du Sud est confronté, en un désir sincère pour les fils de l'Etat naissant d'avancer dans la construction d'un Etat stable. L'étude a révélé que l'Etat de faiblesse du particulier à la lumière des capacités économiques disponibles en présence de l'Etat du Soudan du Sud était dû à l'échec des politiques gouvernementales basées sur le contrôle des ressources de la population qui étaient basées dans ses programmes sur les tribus. et les préjugés ethniques et la privation de nombreux groupes de leurs droits économiques légitimes, ce qui a contribué à la propagation de la violence et au manque de stabilité.